Socialization of the Effect of Variations in Fixation Time of Peripheral Blood Smears (SADT) on Erythrocyte Morphology with Giemsa Staining - Herlina Herlina; Andhika Sentoso; Ajeng prahesti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Peripheral Blood Smear (PBS) examination is a crucial hematology test for evaluating blood cell morphology, particularly that of erythrocytes. The quality of the results is heavily influenced by pre-analytical stages, one of which is the fixation process. Variations in fixation time can affect erythrocyte morphology and staining outcomes; therefore, a proper understanding of the correct procedure is essential. This outreach activity aimed to enhance participants' knowledge and understanding regarding the impact of varying PBS fixation times on erythrocyte morphology when using Giemsa staining. The activity began with a preparation phase involving coordination between the organizing team and the institution regarding the schedule, venue, provision of equipment and materials, and the development of educational content. The implementation phase commenced with participant registration and the opening of the event by the moderator. Following the presentation of the material, a laboratory demonstration was conducted. The organizing team showcased PBS preparations created using methanol fixation times of 1, 3, 5, and 10 minutes. The results indicated that the participants' average knowledge level rose from 59.3% prior to the activity to 95.0% afterward, representing an average increase of 35.7%. The most significant improvement was observed in the understanding of how fixation time variations affect erythrocyte morphology, rising from 47% to 92% (a 45% increase). Appropriate fixation times yielded clearer erythrocyte images, intact cell shapes, and even color distribution, whereas fixation times that were too short or too long compromised the quality of the preparations. This activity successfully broadened participants' insight into the importance of standardizing the fixation process in hematology testing to ensure accurate results that support rapid and precise diagnoses.